Jane Foster's black and white. - Foster, Jane, 1971- (New York, New York : Little Bee Books, 2016)
Illustrations of animals introduce readers to the colors black and white.--
Cover title.
On board pages.
Keywords: Colors -- Juvenile literature; Board books; Color; Board books; Board books; Colors; Juvenile works